Chapter 5 On the Role of the Individual in Materializing, Mediating, and Commemorating Memories of the Stalinist Repressions - Kõresaar, Ene (Taylor & Francis, 2023)
This study combines economic, biographical, performative, and narrative approaches to commemoration to understand how the memory of the Stalinist repressions gains mnemonic capital through individualized practice. It is argued that an individual engaged in the field of commemoration can be seen as a cultural producer and intermediary fulfilling a whole array of different roles, adapting to changing conditions and improvising as the situation demands. The success of the commemorative activities of the organization depends significantly on the material and intangible resources at the disposal of the decision-making individual and the "vernacular creativity" the individual employs. Correspondingly, the selection of symbols used in the commemorative process relies both on the earlier collective mnemonic practices and resources of the national textual community and on the cultural and embodied capital of the decision-making individual. By extending the chains of memory labor outside the field of commemoration, an opportunity has been created for the memory of Stalinist mass repressions to transform and adapt for societal change.